Archives vivantes - Marie Gautheron (Ateliers d'Anthropologie)
Archives vivantes [Living Archives] is a series of filmed interviews shot in Senegal and Benin between 2011 and 2015 as part of a research project called Vivants objets, led by a multidisciplinary team from the École normale supérieure de Lyon. During these interviews, the photographs, histories and museum records of everyday objects collected by the Dakar-Djibouti mission (1931-1933) were presented to artists, culture professionals, and users. As “living archives” of “ethnographic” objects conserved in museums, these films give a palpable sense of the impact of their disappearance (broken transmission, knowledge loss) and return some of their immaterial heritage immediately. They show the interest these objects arouse in the societies that created them, the urgency of a reappropriation process, and question the conditions of their return, or their restitution.